A kind of asphalt mixture based on water damage resistance modified sulfur and preparation method thereof
By polymerizing and modifying sulfur sodium lignin sulfonate, it forms highly polar hydrogen bonds and sulfate, which solves the problems of insufficient water loss resistance and high temperature stability of the modified sulfur asphalt mixture, and significantly improves water stability Performance and mechanical properties and reduce environmental and safety risks during production.
Patent Information
- Application Number
- CN202410583441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-11
AI Technical Summary
When existing modified sulfur asphalt mixtures improve high temperature stability, they have poor water loss resistance, and there are problems of high temperature and harmful gas release during the production process, which affects the environment and the safety of construction workers.
Sodium lignin sulfonate is used to polymerize and modify sulfur to form highly polar hydrogen bonds and sulfate sulfate and sulfone substances, enhance the water stability of the asphalt mixture, and reduce the production temperature and the formation of harmful gases through simplified processes. .
It significantly improves the water stability and mechanical properties of the asphalt mixture, while reducing the production temperature and the generation of harmful gases, and improving the safety and environmental protection of the process.
Smart Images

Figure CN118530001B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road construction materials, and in particular to an asphalt mixture based on water damage resistance modified sulfur and a preparation method thereof. Background Art
[0002] Rutting is one of the main diseases of asphalt roads in my country, which seriously affects driving safety and road performance. As for the asphalt mixture itself, improving the high temperature stability of the asphalt mixture can effectively reduce the occurrence of rutting.
[0003] CN1076386C uses a semi-oxidation method to improve the high-temperature stability of asphalt by increasing the dynamic viscosity of asphalt at 60°C. However, introducing air into asphalt will change the composition structure of asphalt and accelerate the aging of asphalt. In addition, the oxidation method consumes more energy to produce asphalt and generates a large amount of waste gas, which seriously harms human health and the ecological environment. Using sulfur as a modifier can also improve the high-temperature stability of asphalt mixtures. The internal mixing method can replace part of the asphalt, which can effectively alleviate the pressure on resources in the supply of asphalt; However, due to the soaring sulfur price and the fact that sulfur-modified asphalt mixtures will release H during the production process, 2 The problem of sulfur-containing toxic gases such as S has seriously restricted the development of sulfur-to-asphalt technology. CN1690126A discloses a modified sulfur asphalt mixture, which uses light zinc stannate as a smoke inhibitor to prepare modified sulfur, reduces the generation of harmful gases such as sulfur dioxide, hydrogen sulfide and sulfur vapor, and improves the high-temperature stability of asphalt pavement. However, the construction process of the obtained mixture is that the mixing temperature is not higher than 150°C and the paving temperature is not lower than 120°C, which cannot effectively reduce the temperature in the preparation of modified sulfur asphalt mixture, causing great harm to the environment and construction personnel. CN107523072A discloses a warm-mix sulfur asphalt, a mixture containing it and a preparation method thereof, which uses a sweating process to prepare polyethylene wax as a warm-mix agent, reduces the preparation temperature and use temperature of sulfur asphalt, and effectively reduces the generation of harmful gases.
[0004] In addition, in the existing research on modified sulfur asphalt mixture, the focus is usually only on improving the high temperature stability of the mixture, and there are generally problems such as poor water damage resistance. Therefore, there is an urgent need for a modified sulfur asphalt mixture with better water stability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an asphalt mixture based on water-resistant modified sulfur and a preparation method thereof. The asphalt mixture of the present invention can further significantly improve the water stability while maintaining and further effectively improving the good road performance of the modified sulfur asphalt mixture, and has important application and promotion significance. The preparation method of the present invention is simple and easy to operate, and can effectively solve the problems such as insufficient water stability of existing modified sulfur asphalt mixtures for roads.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The first object of the present invention is to provide an asphalt mixture based on water-damage resistant modified sulfur, comprising the following raw materials: mineral material, modified sulfur, and asphalt; the modified sulfur is obtained by polymerizing sulfur with sodium lignin sulfonate.
[0008] The beneficial effect of the present invention is that the asphalt mixture based on water-damage resistant modified sulfur obtained by the present invention can further significantly improve the water stability while maintaining and further effectively improving the good road performance of the modified sulfur asphalt mixture, and has important application and promotion significance.
[0009] Furthermore, the asphalt mixture comprises the following raw materials in percentage by mass: 94.5%-96.5% of mineral material, 1%-1.5% of modified sulfur, and 2.5%-4% of asphalt.
[0010] The beneficial effect of adopting the above further scheme is that the addition of modified sulfur to the asphalt in the present invention will form hydrogen bonds and sulfates and sulfone substances with strong polarity, thereby enhancing the stiffness and high-temperature performance of the asphalt mixture, and this sulfur addition amount has the most significant effect on improving the stiffness of the asphalt.
[0011] Furthermore, the modified sulfur comprises the following raw materials in percentage by mass: 94-98% sulfur and 2%-6% sodium lignin sulfonate.
[0012] The beneficial effects of adopting the above further scheme are: the present invention adopts sodium lignin sulfonate to modify sulfur, and the sodium lignin sulfonate has good diffusion performance, can be dissolved in liquid sulfur under high temperature conditions, and has good chemical stability, which promotes a more uniform and sufficient reaction; and the sodium lignin sulfonate has abundant raw material sources, a simple manufacturing process, and low industrial cost.
[0013] Furthermore, the mineral material comprises the following raw materials in percentage by mass: 96%-98% aggregate and 2-4% filler.
[0014] Furthermore, the aggregate is at least one of basalt, limestone and limestone.
[0015] Furthermore, the filler is at least one of mineral powder, cement and slaked lime.
[0016] The beneficial effect of adopting the above further scheme is that the synthetic gradation of mineral materials meets the recommended range requirements of the current technical specifications for highway asphalt pavement construction in my country; the aggregate can be selected from one or more commonly used aggregates in road projects such as basalt, limestone, limestone, steel slag aggregate, etc., and the filler can be finely ground limestone powder, cement, slaked lime, etc.
[0017] Preferably, when the filler contains mineral powder, the mineral powder is finely ground limestone.
[0018] The second object of the present invention is to provide a method for preparing an asphalt mixture based on water damage resistant modified sulfur, characterized in that the preparation method comprises the following steps:
[0019] (1) sulfur and sodium lignin sulfonate are uniformly mixed, heated for reaction, and then cooled to room temperature to obtain modified sulfur for standby use;
[0020] (2) Weighing asphalt, mineral material, and the modified sulfur respectively and drying them; heating the asphalt, adding the modified sulfur while stirring, and continuing to stir to obtain modified sulfur asphalt mortar;
[0021] (3) drying the aggregate in the mineral material and then heating it, adding the modified sulfur asphalt mortar and the filler in the mineral material and stirring them evenly to obtain the water-resistant modified sulfur-based asphalt mixture.
[0022] The beneficial effects of the present invention are:
[0023] (1) First, sulfur and sodium lignin sulfonate are polymerized under high temperature conditions to connect small sulfur molecules into large molecular long chains. At the same time, sodium lignin sulfonate also has a surface active effect and can reduce the surface tension of water. After the modified sulfur asphalt mortar is fully mixed with the aggregate, the modified sulfur asphalt mortar is wrapped on the surface of the mixture, which can effectively improve the water stability of the asphalt mixture. At the same time, based on the functional group modification effect of sodium lignin sulfonate, the water stability, mechanical properties and high temperature performance of the asphalt mixture can be simultaneously improved.
[0024] (2) Sodium lignin sulfonate has good diffusion properties and can be dissolved in liquid sulfur under high temperature conditions. It also has good chemical stability, which promotes a more uniform and sufficient reaction. In addition, the raw material source of sodium lignin sulfonate is abundant, the manufacturing process is simple, and the industrial cost is low.
[0025] Furthermore, the heating temperature in step (1) is 150° C.-170° C., and the heating time is 3 h-6 h.
[0026] The beneficial effect of adopting the above further scheme is that sulfur and sodium lignin sulfonate undergo polymerization reaction under high temperature conditions, connecting small sulfur molecules into large molecular long chains.
[0027] Furthermore, in step (2), the heating temperature is 120-140° C., and the heating time is 30-60 minutes.
[0028] The beneficial effect of adopting the above further scheme is that at high temperature, sulfur added to asphalt will form hydrogen bonds with strong polarity and sulfates and sulfone substances to produce modified sulfur asphalt mortar.
[0029] Furthermore, step (3) is specifically as follows: adding the modified sulfur asphalt mortar and the filler in the mineral material and stirring them evenly. Specifically, the aggregate in the mineral material is heated and dried at 130°C-140°C for 3h-4h, and at a rotation speed of 2000-2300r / min, first adding the modified sulfur asphalt mortar and stirring for 80-100s, and then adding the filler and continuing to stir for 110-130s. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The SEM test images of Experiment 1 of the present invention; wherein (a) is a SEM image of ordinary sulfur magnified 1000 times; (b) is a SEM image of the modified sulfur in Example 1 magnified 1000 times; (c) is a SEM image of the modified sulfur in Example 2 magnified 1000 times; (d) is a SEM image of the modified sulfur in Example 3 magnified 1000 times; (e) is a SEM image of ordinary sulfur magnified 10000 times; (f) is a SEM image of the modified sulfur in Example 1 magnified 10000 times; (g) is a SEM image of the modified sulfur in Example 2 magnified 10000 times; (h) is a SEM image of the modified sulfur in Example 3 magnified 10000 times;
[0031] Figure 2 These are pictures of preparing asphalt mixtures according to the present invention; wherein (a) is the stirring of asphalt mortar; (b) is the preparation of Marshall specimens; (c) is the freeze-thaw splitting test; and (d) is the Marshall stability test. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0033] Example 1: Preparation of asphalt mixture based on water damage resistance modified sulfur
[0034] (1) Weigh sulfur and sodium lignin sulfonate and mix them evenly (the mass percentage of sulfur is 98% and the mass percentage of sodium lignin sulfonate is 2%), place them in a reaction kettle, heat them to 170° C., keep them warm for 4 hours, and then cool them to room temperature to obtain modified sulfur for later use;
[0035] (2) Weighing 3.7% by weight of AH-70# matrix asphalt, 95.2% by weight of mineral material (the raw materials in the mineral material are: 97% by weight of limestone, 3% by weight of ground limestone powder), and 1.1% by weight of modified sulfur, heating the AH-70# matrix asphalt to 130° C., adding the modified sulfur while stirring, and continuing to stir at a speed of 2000 r / min for 45 min to obtain modified sulfur asphalt mortar;
[0036] (3) The limestone was dried in an oven at 140°C for 4 h, poured into a mixing pot at 140°C for heating, and the modified sulfur asphalt mortar was added and stirred for 90 seconds. Subsequently, the limestone powder was added and stirred for another 120 seconds to obtain a water-resistant modified sulfur asphalt mixture.
[0037] Example 2: Preparation of asphalt mixture based on water damage resistance modified sulfur
[0038] (1) Weigh sulfur and sodium lignin sulfonate and mix them evenly (the mass percentage of sulfur is 96% and the mass percentage of sodium lignin sulfonate is 4%), place them in a reaction kettle, heat them to 170° C., keep them warm for 4 hours, and then cool them to room temperature to obtain modified sulfur for later use;
[0039] (2) Weigh 3.7% by weight of AH-70# base asphalt, 95.2% by weight of mineral material (the raw materials in the mineral material are: 97% by weight of limestone and 3% by weight of ground limestone powder), and 1.1% by weight of modified sulfur, heat the AH-70# base asphalt to 130° C., add the modified sulfur while stirring, and continue stirring at a speed of 2000 r / min for 45 min to obtain modified sulfur asphalt mortar;
[0040] (3) The limestone was dried in an oven at 140°C for 4 h, poured into a mixing pot at 140°C for heating, and the modified sulfur asphalt mortar was added and stirred for 90 seconds. Subsequently, the ground limestone powder was added as filler and stirred for another 120 seconds to obtain a water-resistant modified sulfur asphalt mixture.
[0041] Example 3: Preparation of asphalt mixture based on water damage resistance modified sulfur
[0042] (1) Weigh sulfur and sodium lignin sulfonate and mix them evenly (the mass percentage of sulfur is 94% and the mass percentage of sodium lignin sulfonate is 6%), place them in a reaction kettle, heat them to 170° C., keep them warm for 4 hours, and then cool them to room temperature to obtain modified sulfur for later use;
[0043] (2) Weighing 3.7% by weight of AH-70# matrix asphalt, 95.2% by weight of mineral material (the raw materials in the mineral material are: 97% by weight of limestone, 3% by weight of ground limestone powder), and 1.1% by weight of modified sulfur, heating the AH-70# matrix asphalt to 130° C., adding the modified sulfur while stirring, and continuing to stir at a speed of 2000 r / min for 45 min to obtain modified sulfur asphalt mortar;
[0044] (3) The limestone was dried in an oven at 140°C for 4 h, poured into a mixing pot at 140°C for heating, and the modified sulfur asphalt mortar was added and stirred for 90 seconds. Subsequently, the limestone powder was added and stirred for another 120 seconds to obtain a water-resistant modified sulfur asphalt mixture.
[0045] Comparative Example 1: Preparation of asphalt mixture
[0046] The difference between this comparative example and Example 1 is that the modification of sulfur in step (1) is not performed, and the remaining steps and raw materials are the same as those in Example 1. The specific steps are as follows:
[0047] (1) Weighing 3.7% by weight of AH-70# matrix asphalt, 95.2% by weight of mineral material (the raw materials in the mineral material are: 97% by weight of limestone, 3% by weight of ground limestone powder), and 1.1% by weight of sulfur, heating the AH-70# matrix asphalt to 130° C., adding sulfur while stirring, and continuing to stir at a speed of 2000 r / min for 45 min to obtain sulfur asphalt mortar;
[0048] (2) The limestone was dried in an oven at 140°C for 4 h, poured into a mixing pot at 140°C for heating, sulfur asphalt mortar was added and stirred for 90 seconds, and then the ground limestone powder was added and stirred for another 120 seconds to obtain an asphalt mixture.
[0049] Comparative Example 2: Preparation of asphalt mixture based on water damage resistant modified sulfur
[0050] The difference between this comparative example and Example 1 is that the raw materials used for sulfur modification in step (1) are different, and the remaining steps and raw materials are the same as those in Example 1. The specific step (1) is as follows:
[0051] (1) Weigh sulfur, dipentene, isooctyl acrylate, and an admixture, mix them evenly (the mass percentage of sulfur is 96%, the mass percentage of dipentene is 2%, the mass percentage of isooctyl acrylate is 1.5%, and the mass percentage of the admixture is 0.5%), place them in a reaction kettle, heat them to 170° C., keep them warm for reaction for 4 hours, and then cool them to room temperature to obtain modified sulfur for use.
[0052] Comparative Example 3: Preparation of asphalt mixture based on water damage resistant modified sulfur
[0053] The difference between this comparative example and Example 1 is only that the speed of the stirrer in step (2) is different, and the remaining steps and raw materials are the same as those in Example 1. The specific step (2) is as follows:
[0054] (2) Weigh 3.7% by weight of AH-70# base asphalt, 95.2% by weight of mineral material (the raw materials in the mineral material are: 97% limestone, 3% ground limestone powder), and 1.1% by weight of modified sulfur, heat the AH-70# base asphalt to 130°C, add the modified sulfur while stirring, and continue stirring at a speed of 2500 r / min for 45 minutes to obtain modified sulfur asphalt mortar.
[0055] Test 1: SEM detection:
[0056] Ordinary sulfur, modified sulfur prepared in Example 1, Example 2, and Example 3 were taken and SEM analysis was performed using a TESCAN MIRA3 electron microscope at magnifications of 1000 times and 10000 times, respectively. The SEM analysis results are as follows: Figure 1 shown.
[0057] Depend on Figure 1 We can get:
[0058] The addition of sodium lignin sulfonate can cause a series of chemical reactions or structural changes in sulfur, thereby changing the microscopic morphology of sulfur. Figure 1 (a)-(d) The images magnified 1000 times show that both ordinary sulfur and modified sulfur have lamellar structures. Figure 1 (e)-(h) At a magnification of 10,000 times, Figure 1 The surface of the ordinary sulfur in (e) is rougher than that of the modified sulfur, while the surface of the modified sulfur is smoother. The reason may be that the sodium lignin sulfonate makes the arrangement of the sulfur crystals more orderly and enhances the covalent bond force between the sulfur crystals. Figure 1 (c) Figure 1 (g) There are some tiny holes on the surface, which can adsorb asphalt. Figure 1 (d) Figure 1(h) It can be seen that some sodium lignin sulfonate particles are distributed relatively closely, and some are stacked together, indicating that when the dosage exceeds a certain level, the connection between the sodium lignin sulfonate particles is strong, which is not conducive to uniform dispersion in the asphalt mortar and may reduce the stability of the modified sulfur.
[0059] Test 2: Asphalt mixture performance test
[0060] Various properties of the asphalt mixtures prepared by Examples 1-3 and Comparative Examples 1-3 were tested respectively. The Marshall stability and water immersion residual stability of the asphalt mixtures prepared by Examples 1-3 and Comparative Examples 1-3 were tested using "T0709-2011"; the splitting strength and freeze-thaw splitting strength ratio of the asphalt mixtures prepared by Examples 1-3 and Comparative Examples 1-3 were tested using "T0729-2000"; the dynamic stability of the asphalt mixtures prepared by Examples 1-3 and Comparative Examples 1-3 was tested using "T0729-2000". The results are shown in Table 1.
[0061] Table 1: Performance test results of asphalt mixture
[0062]
[0063] From Table 1, we can get:
[0064] 1. The water-resistant modified sulfur asphalt mixture prepared by the scheme of the present invention, as shown in Examples 1-3, can significantly improve the water stability of the modified sulfur asphalt and simultaneously ensure other performance characteristics; and at a constant speed, the performance curve of the modified asphalt mixture converges with the extension of the stirring time; at a constant stirring time, increasing the mixer speed does not significantly improve the performance of the modified asphalt mixture, so for cost saving considerations, the preparation scheme of the present invention is adopted, and the mixer is controlled to stir at a speed of 2000r / min for 45 minutes; especially when the dosage of sodium lignin sulfonate in Example 3 is 6%, the water immersion residual stability of the obtained asphalt mixture is as high as 96.74%, the splitting strength is 0.99MPa, the freeze-thaw splitting strength ratio can reach 96.64%, and the dynamic stability can reach 3240 times / mm, which can significantly improve the water stability, mechanical properties and high temperature performance of the obtained asphalt mixture.
[0065] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An asphalt mixture based on water-damage-resistant modified sulfur, characterized in that: The asphalt mixture is composed of the following raw materials: mineral material, modified sulfur, and asphalt; the modified sulfur is obtained by polymerizing sulfur with sodium lignin sulfonate; The asphalt mixture is composed of the following raw materials in percentage by mass: 94.5%-96.5% of mineral material, 1%-1.5% of modified sulfur, and 2.5%-4% of asphalt; The modified sulfur is composed of the following raw materials in percentage by mass: 94-98% sulfur and 2%-6% sodium lignin sulfonate.
2. The asphalt mixture based on water damage resistant modified sulfur according to claim 1, characterized in that: The mineral material comprises the following raw materials in percentage by mass: 96%-98% aggregate and 2%-4% filler.
3. The asphalt mixture based on water damage resistant modified sulfur according to claim 2, characterized in that: The aggregate is at least one of basalt, limestone and limestone.
4. The asphalt mixture based on water damage resistant modified sulfur according to claim 2, characterized in that: The filler is at least one of mineral powder, cement and slaked lime.
5. A method for preparing a water-damage resistant modified sulfur asphalt mixture according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing sulfur and sodium lignin sulfonate uniformly, heating for reaction, and cooling to room temperature to obtain modified sulfur for standby use; (2) Weighing asphalt, mineral material, and the modified sulfur respectively and drying them; heating the asphalt, adding the modified sulfur while stirring, and continuing to stir to obtain modified sulfur asphalt mortar; (3) drying the aggregate in the mineral material and then heating it, adding the modified sulfur asphalt mortar and the filler in the mineral material and stirring them evenly to obtain the water-resistant modified sulfur asphalt mixture.
6. The method for preparing asphalt mixture based on water damage resistance modified sulfur according to claim 5, characterized in that: The heating temperature in step (1) is 150° C.-170° C., and the heating time is 3 h-6 h.
7. The method for preparing asphalt mixture based on water damage resistance modified sulfur according to claim 5, characterized in that: The heating temperature in step (2) is 120-140° C., and the heating time is 30-60 minutes.
8. The method for preparing asphalt mixture based on water damage resistance modified sulfur according to claim 5, characterized in that: Step (3) is specifically: adding the modified sulfur asphalt mortar and the filler in the mineral material and stirring them evenly. Specifically, the aggregate in the mineral material is heated and dried at 130°C-140°C for 3h-4h, and at a rotation speed of 2000-2300r / min, first adding the modified sulfur asphalt mortar and stirring for 80-100s, and then adding the filler and continuing to stir for 110-130s.
